2021
DOI: 10.1292/jvms.20-0490
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal motility modulation by stress is associated with reduced smooth muscle contraction through specific transient receptor potential channel

Abstract: Excessive stress response causes disability in social life. There are many diseases caused by stress, such as gastrointestinal motility disorders, depression, eating disorders, and cardiovascular diseases. Transient receptor potential (TRP) channels underlie nonselective cation currents and are downstream effectors of G protein-coupled receptors. Ca 2+ influx is important for smooth muscle contraction, which is responsible for gastrointestinal motility. Little is known about the possible involvement of TRP cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 50 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Diarrhea and constipation are two of the most typical symptoms that appear with stress, and the colon is involved in these [ 10 ]. In a previous report, we reported that water immersion restraint stress affected small intestinal motility in mice [ 3 ], however we did not analyse colon motility. Based on this background, the purpose of this study is to measure the changes in colon motility due to stress.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Diarrhea and constipation are two of the most typical symptoms that appear with stress, and the colon is involved in these [ 10 ]. In a previous report, we reported that water immersion restraint stress affected small intestinal motility in mice [ 3 ], however we did not analyse colon motility. Based on this background, the purpose of this study is to measure the changes in colon motility due to stress.…”
mentioning
confidence: 99%
“…Water immersion restraint stress was performed as described previously [ 3 ] with some modifications. Male C57BL/6 mice (8–10 weeks old) were purchased from CLEA Japan, Inc. (Tokyo, Japan).…”
mentioning
confidence: 99%
See 3 more Smart Citations